2012
DOI: 10.1007/s12022-012-9223-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Stromal Cell-Derived Factor 1 and CXCR7 in Papillary Thyroid Carcinoma

Abstract: Stromal cell-derived factor 1 (SDF-1) is a chemokine that is expressed in some cancer cells and is involved in tumor cell migration and metastasis. CXCR7, a novel receptor for SDF-1, has been identified recently. Researches demonstrated that interaction between SDF-1 and CXCR7 could play an important role in cancer progression. In this study, we aimed to investigate the expressions of SDF-1 and CXCR7 and the relationship between their expressions and clinicopathological characteristics in papillary thyroid car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…24,38 CXCL12/SDF-1 and its novel receptor CXCR7 have been found in PTC patients. 47 Interestingly, CXCL12 expression was exclusively found in PTCs compared to other thyroid lesions and displayed high sensitivity, specificity, positive and negative predictive values. For these reasons CXCL12 has been proposed as a novel diagnostic marker for PTC.…”
Section: Chemokinesmentioning
confidence: 93%
“…24,38 CXCL12/SDF-1 and its novel receptor CXCR7 have been found in PTC patients. 47 Interestingly, CXCL12 expression was exclusively found in PTCs compared to other thyroid lesions and displayed high sensitivity, specificity, positive and negative predictive values. For these reasons CXCL12 has been proposed as a novel diagnostic marker for PTC.…”
Section: Chemokinesmentioning
confidence: 93%
“…Previous studies from our group demonstrated that overexpression of CXCR7 in PTC tissue was positively associated with lymph node metastasis, whereas knockdown of CXCR7 in PTC cells suppressed cell proliferation and invasion, and promoted apoptosis (11,12). Furthermore, gene expression profile analysis demonstrated that CXCR7 activates the PI3K/AKT/NF-κB CXCR7, C-X-C chemokine receptor type 7; FN1, fibronectin 1; BSG, basigin; PPL, periplakin; TAGLN2, transgelin-2; AHNAK2, AHNAK nucleoprotein 2; SERPINB5, serpin family B member 5.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have demonstrated that C-X-C chemokine receptor type 7 (CXCR7) expression serves a role in tumor cell proliferation, angiogenesis, invasion and metastasis (7)(8)(9)(10). A previous study from our laboratory demonstrated that CXCR7 was overexpressed in PTC tissue compared with peritumoral non-malignant tissue and benign thyroid lesion tissue, and the expression of CXCR7 was positively associated with cervical lymph node metastasis (11). Furthermore, knockdown of CXCR7 in PTC cells has been demonstrated to suppress cell proliferation and invasion, and promote apoptosis (12), which suggests that CXCR7 is involved in the regulation of PTC progression.…”
Section: Introductionmentioning
confidence: 97%
“…CXCR7, as a recently discovered chemokine receptor, has demonstrated its characteristics in six aspects out of the ten top hallmarks of tumors, including resisting cell death, inducing angiogenesis, sustaining proliferative signaling, activating invasion and metastasis, tumor-promoting inflammation, and cancer-related genes [14,[17][18][19][20][21][22]. Both CXCR4 and CXCR7 are receptors of chemokine CXCL12 and have been reported in multiple tumor types.…”
Section: Discussionmentioning
confidence: 99%